2017
DOI: 10.3847/1538-4365/aa80e4
|View full text |Cite
|
Sign up to set email alerts
|

The Ages and Masses of a Million Galactic-disk Main-sequence Turnoff and Subgiant Stars from the LAMOST Galactic Spectroscopic Surveys

Abstract: We present estimates of stellar age and mass for 0.93 million Galactic disk main sequence turn-off and sub-giant stars from the LAMOST Galactic Spectroscopic Surveys. The ages and masses are determined by matching with stellar isochrones using Bayesian algorithm, utilizing effective temperature T eff , absolute magnitude M V , metallicity Gyr exhibit both the thin and thick disk sequences, while younger (older) stars show only the thin (thick) disk sequence, indicating that the thin disk became prominent 8-10 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
92
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 96 publications
14
92
1
Order By: Relevance
“…There is an increased dominance of young stars in the outer disc at all |z| heights. This dominance of young stars in the outer Galaxy has been observed using APOGEE (Ness et al 2016) and LAMOST (Xiang et al 2017). It is likely related to the decreased relative contribution in the outer disc of the high-α sequence, which has been found to be generally older than the low-α sequence.…”
Section: Metallicity-age Relationmentioning
confidence: 60%
See 1 more Smart Citation
“…There is an increased dominance of young stars in the outer disc at all |z| heights. This dominance of young stars in the outer Galaxy has been observed using APOGEE (Ness et al 2016) and LAMOST (Xiang et al 2017). It is likely related to the decreased relative contribution in the outer disc of the high-α sequence, which has been found to be generally older than the low-α sequence.…”
Section: Metallicity-age Relationmentioning
confidence: 60%
“…However, the change in the turnover feature with increasing |z|, could also be caused by a lack of young stars at high |z|. The 7 < R Gal < 9, 1 <|z|< 2 bin is dominated by the high-α sequence, which has been found to be uniformly old (see Figure 7 and Xiang et al 2017).…”
Section: Metallicity-age Relationmentioning
confidence: 95%
“…It has also been suggested that the mismatch is also metallicity dependent (e.g. Xiang et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…RAVE (Steinmetz et al 2006), SEGUE (Yanny et al 2009), LAMOST Zhao et al 2012), Gaia-ESO (Gilmore et al 2012), GALAH (De Silva et al 2015), APOGEE (Majewski et al 2017), and the Gaia Radial Velocity Spectrometer (Cropper et al 2018); as well as email: mxiang@mpia.de * Hubble fellow upcoming surveys such as SDSS-V (Kollmeier et al 2017), 4MOST (Feltzing et al 2018;de Jong et al 2019), and WEAVE (Dalton et al 2014). These spectroscopic surveys, combined with the astrometric and photometric information from the Gaia mission (Gaia Collaboration et al 2016Collaboration et al , 2018, make it possible for us to obtain precise and accurate information for millions of stars in phase space or orbit space, along with estimates of age, mass, metallicity, and abundances for many elements, providing unprecedented opportunities to unravel the assemblage and evolution history of our Galaxy (see e.g., Rix & Bovy 2013;Ting, Conroy & Goodman 2015;Xiang et al 2017aXiang et al , 2018Frankel et al 2018;Bland-Hawthorn et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is generally understood in terms of the existence of a chemical "thick disk" (Yoshii 1982;Gilmore & Reid 1983) that comprises largely old stars enhanced in the α elements, along with a younger chemical "thin disk" of roughly solar abundance (e.g. Chiappini et al 1997;Bensby et al 2003;Haywood et al 2013;Xiang et al 2017;Wu et al 2019).…”
mentioning
confidence: 99%